Religious Values-Based Learning Materials on Earth and Space Science: Analysis Spirituality and Conceptual Understanding Levels - Rukmana, Diki; Suhandi, Andi; Ramalis, Taufik Ramlan; Samsudin, Achmad (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to determine the effect of religious values-based earth and space science teaching materials on the level of mastery of concepts and spiritual attitudes. Using one group pretest-posttest design, 14 items of concept understanding essays test and 15 items of spiritual attitude questionnaire were given to 32 prospective elementary school science teachers who took earth and space science courses in the even semester of 2021/2022. The results of data analysis showed that 30.13% of prospective teacher an increase to the level of partial understanding and 34.60% of prospective teacher an increase to the level of sound understanding. In the aspect of spiritual attitudes, 91.25% of prospective teacher have the perception that their spiritual level has increased and 8.75% of prospective teacher have the perception that their spiritual level is fixed. These results indicate that the religious value-based science teaching materials used are good enough to increase the level of conceptual understanding and spiritual attitudes